2014
DOI: 10.3109/13625187.2014.907398
|View full text |Cite
|
Sign up to set email alerts
|

A survey on Swiss women's preferred menstrual/withdrawal bleeding pattern over different phases of reproductive life and with use of hormonal contraception

Abstract: Contraceptive counsellors should be aware that women's wishes differ widely. Predictability of bleeding seems to be more important to them than postponing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 27 publications
1
27
0
Order By: Relevance
“…There is a lack of relevant studies in the scientific databases, including Medline and Scopus concerning the three countries involved in the present survey: Hungary, Romania and Serbia. Previous surveys in women of reproductive age regarding their menstrual bleeding patterns have revealed that women in different countries in Europe share similar views about the 'necessity' of menstruation, with approximately 30% of the responders preferring not having menstrual bleeding at all (Tyden et al 2006;Fruzetti et al 2008;Merki-Feld et al 2014). Students in the present three countries are of particular interest as the availability of contraceptive methods prospered in this region in the last 20 years.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…There is a lack of relevant studies in the scientific databases, including Medline and Scopus concerning the three countries involved in the present survey: Hungary, Romania and Serbia. Previous surveys in women of reproductive age regarding their menstrual bleeding patterns have revealed that women in different countries in Europe share similar views about the 'necessity' of menstruation, with approximately 30% of the responders preferring not having menstrual bleeding at all (Tyden et al 2006;Fruzetti et al 2008;Merki-Feld et al 2014). Students in the present three countries are of particular interest as the availability of contraceptive methods prospered in this region in the last 20 years.…”
Section: Introductionmentioning
confidence: 84%
“…There have been a number of studies published on the knowledge and attitudes related to the menstrual cycle, child-bearing and contraception in different populations, but there have been none in South Eastern Europe recently (Inandi et al 2003;Tyden et al 2006;Fruzetti et al 2008;Merki-Feld et al 2014). There is a lack of relevant studies in the scientific databases, including Medline and Scopus concerning the three countries involved in the present survey: Hungary, Romania and Serbia.…”
Section: Introductionmentioning
confidence: 99%
“…What is important to many women is how manageable their bleeding is, impinging as little as possible on daily activities and quality of life. The majority of women prefer to have fewer bleeding days and less heavy bleeding [1,2,17]. Only 37% wanted monthly bleeding [18].…”
Section: Discussionmentioning
confidence: 99%
“…Only 37% wanted monthly bleeding [18]. Around 30% of women feel that menstrual bleeding has a severe negative impact on their daily life [2,17]. In a recent Swiss survey, 80% of the participants wanted fewer bleeding days while using a contraceptive [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation